The Social and Individual Characteristics of Women Associated With Engagement With Multiple Intimate Violent Partners. Issue 21 (November 2019) - Stein, Sara F.; Grogan-Kaylor, Andrew A.; Galano, Maria M.; Clark, Hannah M.; Graham-Bermann, Sandra A.
Intimate partner violence (IPV) is a serious public health problem with known negative physical and mental health outcomes for women exposed. Studies have shown that with increased violence exposure, there are increased risks of negative outcomes for women. Likewise, chronicity of IPV across multiple partners is linked to more profound psychological suffering than acute exposure. However, little is known about the social- and individual-level characteristics of women that are correlated with engagement with multiple abusive partners. The current study ( N = 164) identifies the characteristics of women that are associated with the number of violent partners with which they have been involved, with 35% of the sample reporting multiple IPV relationships. Participants reported on the number of violent partners, demographic characteristics, trauma history, current trauma and depressive symptoms, and exposure to IPV, including physical, sexual, and psychological violence. Results of multiple regression analysis indicate that trauma history (childhood sexual abuse, being held hostage, and torture) and current psychological violence were associated with women's engagement with multiple violent partners. Additional findings reveal that identification as African American and White was associated with greater re-engagement compared with identification as Latina. Finally, current exposure to sexual violence was associated with fewer violent partners. The clinical implications of these findings for treatment for women at risk for engagement with multiple partners in IPV relationships are discussed.